2016
DOI: 10.1177/0954008316644036
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermal conductivity of epoxy composites prepared with a mixed filler of multiwalled carbon nanotubes and aluminum nitride particles

Abstract: The thermal conductive filler/epoxy resin (EP) composites were prepared by a casting method. The effects of the multiwalled carbon nanotubes (MWCNTs), aluminum nitride (AlN) particles, and their compounds on the microstructure and thermal conductivity of the composites were investigated, in addition to the thermal properties. The results indicated that compounds of MWCNTs and AlN particles exhibited a remarkable synergistic effect to improve the thermal conductivity properties of the composites. The one-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
(38 reference statements)
0
22
1
Order By: Relevance
“…Development of different inorganic nanofillers such as silica, alumina, titania, zirconia, silicon nitride, and silicon carbide with improved performance has been widely studied with much success. 1418 Advancement in nanotechnology promotes the mass production of nanosized silica, which has been widely used as fillers in engineering composites. Many studies concerning silica-filled epoxy resins showed that the resins exhibited lower shrinkage on curing, lower thermal expansion coefficient, better thermal conductivity, and improved mechanical properties due to the silica-particle filling.…”
Section: Introductionmentioning
confidence: 99%
“…Development of different inorganic nanofillers such as silica, alumina, titania, zirconia, silicon nitride, and silicon carbide with improved performance has been widely studied with much success. 1418 Advancement in nanotechnology promotes the mass production of nanosized silica, which has been widely used as fillers in engineering composites. Many studies concerning silica-filled epoxy resins showed that the resins exhibited lower shrinkage on curing, lower thermal expansion coefficient, better thermal conductivity, and improved mechanical properties due to the silica-particle filling.…”
Section: Introductionmentioning
confidence: 99%
“…The data is shown as a function of filler volume fraction. Notably, data from [11], [13] and [15], and the initial data point from [14] appear to collapse approximately onto a single straight line. An attempt was made to predict the experimental thermal conductivity data of nanocomposites shown in Fig.1.…”
Section: Validation and Verfication Of Modelsmentioning
confidence: 96%
“…The enhancement value was higher than that by individual CNT; this was because the hybridized Al-CNT could improve the compatibility between the filler and the matrix and could reduce the modulus mismatch at the interface. Jiao et al investigated the synergistic effects of multiwalled carbon nanotubes and aluminum nitride particles on the thermal conductivity of epoxy composites [85]. Results showed that the 1D MWCNTs with superb thermal conductivity and large aspect ratio easily bridged the isolated AlN particles to Large particle (!F 2 / 3 )…”
Section: The Synergistic Effect Of 1d Nanomaterials and 0dmentioning
confidence: 99%